Definitions, Epidemiology, Clinical Risk Factors, and Health Disparities in Acute Respiratory Distress Syndrome - Kang, Mohleen; Kempker, Jordan A. (Seminars in Respiratory and Critical Care Medicine, 2019)
Acute respiratory distress syndrome (ARDS) is a syndrome of inflammatory lung injury currently defined as the rapid onset of hypoxemia and radiographic opacities from a recent direct or indirect insult that is not explained by other causes. While the diagnostic criteria used to define ARDS are helpful in the clinical setting, they are not entirely specific for the characteristic pathophysiology of diffuse alveolar lung damage. This case definition introduces challenges to the reliable and accurate epidemiologic study of the condition. Within these limitations, ARDS appears to be a condition that is relatively rare within the general population but common within the context of the intensive care unit. Furthermore, the frequency and outcomes of ARDS seem to vary between populations, with no clearly discernible temporal trends in incidence or case fatality that are uniform across studies.
Keywords: Acute Respiratory Distress Syndrome; ARDS; epidemiology; health disparities